2018
DOI: 10.1088/0256-307x/35/12/127501
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and topological transitions in three-dimensional topological Kondo insulator

Abstract: By using an extended slave-boson method, we draw a global phase diagram summarizing both magnetic phases and paramagnetic (PM) topological insulating phases (TIs) in three-dimensional topological Kondo insulator (TKI). By including electron hopping (EH) up to third neighbor, we identify four strong topological insulating (STI) phases and two weak topological insulating (WTI) phases, then the PM phase diagrams characterizing topological transitions between these TIs are depicted as functions of EH, f -electron … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…This mechanism of FOVT in PAM is very similar to that of Falicov-Kimball model, since in both models the U fc term plays a crucial role in generating the FOVT [46][47][48][49]. Previous works have shown that the variation of f or V can lead to a sign reversal of the parity at certain TRIM through closing and reopening of bulk insulating gap, resulting in successive topological transitions [5,7,24]. Consequently, both STI and WTI can be further classified according to their bandinversion points (or the locations of Dirac points) [7,23,24].…”
Section: Valence Transition and Topological Transitionssupporting
confidence: 55%
See 3 more Smart Citations
“…This mechanism of FOVT in PAM is very similar to that of Falicov-Kimball model, since in both models the U fc term plays a crucial role in generating the FOVT [46][47][48][49]. Previous works have shown that the variation of f or V can lead to a sign reversal of the parity at certain TRIM through closing and reopening of bulk insulating gap, resulting in successive topological transitions [5,7,24]. Consequently, both STI and WTI can be further classified according to their bandinversion points (or the locations of Dirac points) [7,23,24].…”
Section: Valence Transition and Topological Transitionssupporting
confidence: 55%
“…In Fig. 2b, the phase diagram around the QCP is shown in enlarged pattern, in which the FOVT successively converges with the topological boundaries at two points, one at U f c =4.38 and ǫ f =−2.93, the other at U f c =4.82 and ǫ f =−3.19, separating the FOVT into three segments: (1) when 4.31< U f c <4.38, FOVT occurs near conventional STIΓ X -WTI X transition ( the subscripts denote the Dirac points on the surface Brillouin zone 47 ); (2) when 4.38< U f c <4.82, FOVT occurs simultaneously with first-order STIΓ X -WTI X transition; (3) when U f c >4.82, a first-order STIΓ X -STI M transition takes place at FOVT. Below the QCP, namely when U f c <4.31, U f c is insufficient to produce FOVT, but rather a valence crossover between Kondo region and MV.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Layers of group IV elements, known as silicene, [10][11][12] germanene, [13] stanene, [14,15] and layers of a group III element, i.e., borophenes, [16][17][18] as well as group V fewlayers, i.e., 2D P, [19][20][21][22][23] As, [24] Sb, [25] and Bi, [26] were subsequently predicted and synthesized or isolated. These mono-and few-layers of groups III, IV, and V elements were experimentally shown or were theoretically predicted to have tunable bandgap, [7,12,23,24] high carrier mobility, [19][20][21]25] strong light absorption and response in infrared and visible lights ranges, [27,28] exceptional mechanical and frictional properties, [5,17,22] catalysis activities, [29] topological electronic states, [8,10,14,26,[30][31][32][33][34][35] superconductivity, [36,37] and among the others. [38] However, the few-layer forms of group VI elements are still ambiguous and are yet to be unveiled.…”
Section: Introductionmentioning
confidence: 99%